Crossing Highbridge : a memoir of Irish America - Waters, Maureen, 1939- (Irish studies (Syracuse, N.Y.), 2001)
An evocative tale of coming to womanhood in the disorienting 1960s- a girl in the world of nuns and the Holy Ghost- but on a deeper level, this is a story of a woman who has suffered unimaginable loss and attempts to make sense of that loss by re-imagining her past and her own Irish-American heritage. The first in her family born in the United States, Maureen grew up the Bronx Irish daughter of two unforgettable immigrants: her storytelling, former revolutionary father, and her fierce, IRA-supporting mother. Crossing Higbbridge is framed by the accidental death of Waters's son and her struggle to make sense of this loss by re-imagining her past and her heritage. Her life in postwar New York City was colored by Catholicism and strong cultural links to the other side - by Irish step dancing, the melodies of Thomas Moore, and the rituals, inflections, and harrowing memories impressed on her. Sex was a mystery. Schoolgirls wore below-the-knee blue serge uniforms with starched white collars and cuffs. Brutal treatment at the hands of the hands of the nuns who ran her college drove Waters to transfer to a secular school. Waters rebelled against an upbringing that seemed to wall her off from the 20th century. She left the church, married, divorced, and became a scholar and professor at the City University of New York. Waters follows in the tradition of her father with this vividly humorous and moving story. -- Publisher description